Metal Atom Dynamics in Superbulky Metallocenes: A Comparison of (CpBIG)2Sn and (CpBIG)2Eu - Harder, Sjoerd; Naglav, Dominik; Schwerdtfeger, Peter; Nowik, Israel; Herber, Rolfe H. (Inorganic Chemistry, 2014)
CpSn (Cp = (4-n-Bu-C H)cyclopentadienyl), prepared by reaction of 2 equiv of CpNa with SnCl, crystallized isomorphous to other known metallocenes with this ligand (Ca, Sr, Ba, Sm, Eu, Yb). Similarly, it shows perfect linearity, C-H···C(π) bonding between the Cp rings and out-of-plane bending of the aryl substituents toward the metal. Whereas all other CpM complexes show large disorder in the metal position, the Sn atom in Cp Sn is perfectly ordered. In contrast, Sn and Eu Mößbauer investigations on the corresponding CpM metallocenes show that Sn(II) is more dynamic and loosely bound than Eu(II). The large displacement factors in the group 2 and especially in the lanthanide(II) metallocenes CpM can be explained by static metal disorder in a plane parallel to the Cp rings. Despite parallel Cp rings, these metallocenes have a nonlinear Cp-M-Cp geometry. This is explained by an ionic model in which metal atoms are polarized by the negatively charged Cp rings. The extent of nonlinearity is in line with trends found in M ion polarizabilities. The range of known calculated dipole polarizabilities at the Douglas-Kroll CCSD(T) level was extended with values (atomic units) for Sn 15.35, Sm (4fF) 9.82, Eu(4fS) 8.99, and Yb(4fS) 6.55. This polarizability model cannot be applied to predominantly covalently bound CpSn, which shows a perfectly ordered structure. The bent geometry of CpSn should therefore not be explained by metal polarizability but is due to van der Waals Cp···Cp* attraction and (to some extent) to a small p-character component in the Sn lone pair. © 2014 American Chemical Society.